Desenvolvimento de um sensor amperométrico baseado em ftalocianina de ferro, nanotubo de carbono oxidado e óxido de grafeno para determinação de isoniazida - Spindola, Rolff Ferreira (2016)
A novel platform for electroanalysis of isoniazid based on multi-walled carbon nanotube oxide and graphene oxide composite as support to iron phthalocyanine (MWCNTO-GO/FePc) has been developed. The FePc/MWCNTO-GO modified electrode is sensible for isoniazid, decreasing substantially its oxidation potential to + 200 mV vs. Ag/AgCl. Electrochemical and electroanalytical properties of the FePc/MWCNTO-GO modified electrode were investigated by cyclic voltammetry, electrochemical impedance spectroscopy, scanning electrochemical microscopy, and amperometry. The sensor presents better performance in 0,1 mol L-1 phosphate buffer at pH 7,4. Under optimized conditions, a linear response range from 5 μmol L-1 to 476 µmol L-1 was obtained with a sensitivity of 0,0225 μA L μmol-1. The limits of detection and quantification for isoniazid determination were 0,56 μmol L-1 and 1,88 μmol L-1, respectively. The relative standard deviation for 10 determinations of 100 μmol L-1 isoniazid was 2,5%. The sensor was successfully applied for isoniazid determination in artificial body fluids.